1991
DOI: 10.1111/j.1440-1673.1991.tb03049.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Neuroblastoma ‐ Management of a rare tumour at the Queensland Radium Institute and literature review

Abstract: Olfactory neuroblastoma (esthesioneuroblastoma) is an extremely rare tumour arising from the olfactory epithelium of the nasal cavity close to the cribriform plate. Most institutions will have little experience in recognising the clinical and histological features, or management of this tumour and reliance is placed on researching the literature when the individual patient presents. This study reviews seven patients with olfactory neuroblastoma treated at the Queensland Radium Institute from 1971 to January 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…Our 5‐ and 10‐year survival rates of 87.9% and 69.2%, respectively, compare favorably with the literature. In a meta‐analysis3 of 25 studies of 390 of patients the reported overall survival at 5 years was 45%, with extremes of 86%28, 29 and 0% 29. However, the authors noted that for the larger studies the survival rates approximated 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Our 5‐ and 10‐year survival rates of 87.9% and 69.2%, respectively, compare favorably with the literature. In a meta‐analysis3 of 25 studies of 390 of patients the reported overall survival at 5 years was 45%, with extremes of 86%28, 29 and 0% 29. However, the authors noted that for the larger studies the survival rates approximated 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Overall survival at 5 years could be extracted from 25 studies; the mean was 45% (SD 22), with extremes of 86% 58 and zero. 57 Disease-free survival at 2 years was found in 17 studies, 2,43,[54][55][56][57][58]60,62,65,66,[68][69][70][71]73,78 that at 3 years in 20 reports 4,6,8,43,[54][55][56][57][58]60,62,65,66,[68][69][70][71][72][73]78 and that at 5 years in 24 publications. 2,4,6,8,43,[54][55][56][57][58][60][61]…”
Section: Resultsmentioning
confidence: 99%
“…The 26 studies 2,[4][5][6]8,43,[54][55][56][57][58][60][61][62][63][64][65][66][68][69][70][71][72][73]77,78 reported on 390 patients with ENB. Overall survival at 5 years could be extracted from 25 studies; the mean was 45% (SD 22), with extremes of 86% 58 and zero.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature the 5-year recurrence free survival is report to be between 52% and 90% 16,29,40 . ENB recurs locally in up to 60% of patients who undergo surgery 15 , and its locally aggressive behavior is the most common cause of death 44 . Median survival after recurrences was only 12 months 45,46 .…”
Section: Discussionmentioning
confidence: 99%